2020
DOI: 10.15585/mmwr.mm6949a3
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 Mortality Among American Indian and Alaska Native Persons — 14 States, January–June 2020

Abstract: American Indian/Alaska Native (AI/AN) persons experienced disproportionate mortality during the 2009 influenza A(H1N1) pandemic (1,2). Concerns of a similar trend during the coronavirus disease 2019 (COVID-19) pandemic led to the formation of a workgroup* to assess the prevalence of COVID-19 deaths in the AI/AN population. As of December 2, 2020, CDC has reported 2,689 COVID-19associated deaths among non-Hispanic AI/AN persons in the United States. † A recent analysis found that the cumulative incidence of lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 6 publications
2
80
0
Order By: Relevance
“…An assessment of the impact of COVID-19 among AI/AN persons from 23 states made early during the pandemic (January–July 2020) found that the cumulative incidence rate ratio between AI/AN and White persons was 3.5 ( 2 ), similar to the current study’s finding. In addition, a study comparing age-adjusted COVID-19 mortality rates among AI/AN and White persons in 14 states during January–June 2020 reported a mortality rate ratio of 1.8 for AI/AN persons compared with that for White persons ( 3 ), which was lower than that identified in a supplementary analysis conducted by MDPHHS. ¶¶…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…An assessment of the impact of COVID-19 among AI/AN persons from 23 states made early during the pandemic (January–July 2020) found that the cumulative incidence rate ratio between AI/AN and White persons was 3.5 ( 2 ), similar to the current study’s finding. In addition, a study comparing age-adjusted COVID-19 mortality rates among AI/AN and White persons in 14 states during January–June 2020 reported a mortality rate ratio of 1.8 for AI/AN persons compared with that for White persons ( 3 ), which was lower than that identified in a supplementary analysis conducted by MDPHHS. ¶¶…”
Section: Discussionmentioning
confidence: 90%
“…Geographic differences in infectious disease mortality rates have been observed among American Indian or Alaska Native (AI/AN) persons in the United States ( 1 ), and aggregate analyses of data from selected U.S. states indicate that COVID-19 incidence and mortality are higher among AI/AN persons than they are among White persons ( 2 , 3 ). State-level data could be used to identify disparities and guide local efforts to reduce COVID-19–associated incidence and mortality; however, such data are limited.…”
mentioning
confidence: 99%
“…CDC data show that AI/ANs are 3.5 times more likely to contract COVID-19 and to be hospitalized than non-Hispanic Whites in the United States ( Center for Disease Control and Prevention, 2020b ; Center for Disease Control and Prevention, 2020c ; Center for Disease Control and Prevention, 2020d ; Hatcher et al, 2020 ). Additionally, the age adjusted mortality rate for COVID-19 was 1.8 times higher in AI/ANs than in non-Hispanic Whites ( Arrazola et al, 2020 ). As with all races, COVID-19 mortality rates appear to be increasing with age for AI/AN peoples, but the largest mortality disparity between AI/ANs and non-Hispanic whites is in the age group of 20–49 years ( Arrazola et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the age adjusted mortality rate for COVID-19 was 1.8 times higher in AI/ANs than in non-Hispanic Whites ( Arrazola et al, 2020 ). As with all races, COVID-19 mortality rates appear to be increasing with age for AI/AN peoples, but the largest mortality disparity between AI/ANs and non-Hispanic whites is in the age group of 20–49 years ( Arrazola et al, 2020 ). COVID-19 mortality rates by both sexes for AI/ANs are 1.8 times that of non-Hispanic Whites of the respective sex ( Arrazola et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation